Effect of pore-throat structure and displacement pressure on gas distribution in tight sandstone reservoirs of the Lower Shihezi Formation in the Ordos Basin, China - Bao, Lei; Chen, Qi; Liu, Yuming; Hou, Jiagen; Zhang, Zhanyang (Frontiers in Earth Science, 2026)
To quantitatively analyze the effects of different displacement pressures and pore-throat structures on gas distribution characteristics, this study conducted multi-pressure gas displacement water NMR experiments and high-pressure mercury injection tests on twelve tight sandstone samples from the Lower Permian Shihezi Formation in the northern Ordos Basin. Based on the classification of pore-throat structures, quantitative analyses were performed. The study shows that four lithofacies are identified: braided channel base pebbly coarse-grained sandstone (Lpc), medial bar medium to coarse grained sandstone (Lmc), bar edge medium sandstone (Lm), and levee medium to fine grained sandstone (Lmf). The corresponding pore-throat structures and spatial types (nanopores, micropores and mesopores) are also determined. Mesopores are the primary storage spaces for gas, with an average gas saturation of 70%. At the microscopic level, median pore-throat radius (Rm), homogeneity coefficient (Hc), and sorting coefficient (Sc) significantly influence gas distribution within pore-throat of different sizes, while brittle mineral content and petrophysical parameters mainly affect gas content in mesopores. With increasing displacement pressure, the gas displacement rate in pores decreases exponentially, and at a displacement pressure of 6 MPa, the gas saturation of all types of reservoirs can reach 80% of the final gas saturation. Based on these findings, the gas distribution characteristics of various lithofacies of tight sandstones deposited by a continental braided river sedimentary system are established, identifying pebbly coarse-grained sandstone and medium-coarse sandstone as the optimal lithofacies for gas-bearing potential.